Health Care for LGBTQ+ Youth: A Case-Based Workshop for Medical Students and Pediatric Residents - Michael J. Luke; Gabrielle Jasmin; Keven I. Cabrera; Neal D. Hoffman; Lauren T. Roth (Association of American Medical Colleges, 2024)
Introduction Undergraduate medical education and graduate medical education lack formal curricula on providing care for lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ+) youth. The onset of the COVID-19 pandemic has led to further challenges in delivering engaging, patient-centered education on LGBTQ+ health. Methods We developed a 90-minute case-based LGBTQ+ health curriculum delivered twice: to fourth-year medical students (in person only) and to pediatric residents (in-person and virtual options). Learners worked in small groups to engage in self-directed learning to review cases with associated questions, followed by a faculty-facilitated discussion and didactic component. Additionally, residents received a 45-minute patient-and-caregiver panel to explore lived experiences within the trans and nonbinary community. Retrospective pre-post surveys assessing knowledge, comfort, and perceived clinical impact were analyzed via paired t tests and descriptive statistics. Results Sixty-two learners completed our evaluation, including 19 residents and 43 medical students. After the curriculum, we noted significant improvement in learners' perceived knowledge and comfort in all surveyed competencies; >90% of learners noted the curriculum was well organized and engaging, with the patient-caregiver panel marked as a highlight. Discussion A multimodal curriculum using case-based, problem-based learning and a patient-caregiver panel can be a promising method of providing interactive and up-to-date education on LGBTQ+ health care. This model can also be used to provide education on other medical education topics that are constantly evolving and lack national standardization.